2003
DOI: 10.1016/j.sbi.2003.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The positions of radical intermediates in the active sites of adenosylcobalamin-dependent enzymes

Abstract: The radical intermediates generated during the catalytic cycles of adenosylcobalamin-dependent enzymes occur in pairs. The positions of radicals residing on the cofactor, substrate or protein, relative to the position of the low-spin Co 2+ from the cob(II)alamin intermediate, can be extracted from electron paramagnetic resonance (EPR) spectra of the spin-coupled pairs. Examples of radical-Co 2+ pairs that span a range of interspin distances from 3 to 13 Å have been presented. Interspin distances greater than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The positions of radical intermediates in the active sites were reviewed by Reed and Mansoorabadi [82]. The first direct proof of radical mechanism in these enzymes was obtained in the reaction of the substrate homologue 2,4-DAB with 4,5-OAM only five years back [70].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…The positions of radical intermediates in the active sites were reviewed by Reed and Mansoorabadi [82]. The first direct proof of radical mechanism in these enzymes was obtained in the reaction of the substrate homologue 2,4-DAB with 4,5-OAM only five years back [70].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…the low spin Co 2ϩ and the substrate/product intermediate) formed during turnover of AdoCbl-dependent enzymes is a function of their separation and relative orientation (10). Analysis of the EPR signatures from Class I and II isomerases reveals that the former have strong exchange-coupled spin systems, indicating an interspin distance of Ͻ6 Å (22,35,36), whereas the latter exhibit a weakly coupled spin system, reflecting a larger distance (11-13 Å) between the paramagnetic centers (30,37).…”
Section: Cob(ii)alamin Is Formed Only Transiently Upon Reactionmentioning
confidence: 99%
“…In the presence of substrate, cob(II)alamin accumulates at a steady-state concentration, which can be observed by EPR and UV-visible spectroscopy. Class I and Class II isomerases have been extensively studied, and the cob(II)alamin spectroscopic signature has been valuable in studies of mechanism (6,8,10). Lysine 5,6-aminomutase (5,6-LAM) is the only Class III enzyme for which detailed studies of mechanism are reported.…”
mentioning
confidence: 99%
“…In particular, the apparent g values in the spectrum and the magnitude of the 59 Co hyperfine splitting are similar to those found for other cob(II)alamin-organic radical triplets in AdoCbl-dependent enzymes (9). The appearance of the EPR spectra in these hybrid triplet systems is dependent on the separation between Co 2+ and the organic radical and on the position of the organic radical in the g-axis system of Co 2+ (9,25,26). The radical rearrangement that is outlined in Figure 1 includes the primary alkyl radicals, the 5′-deoxyadenosyl radical and the methylmalonyl-CoA radical, and a secondary alkyl radical, the succinyl-CoA radical.…”
Section: Analysis Of the Epr Patternmentioning
confidence: 99%